Seashell discs from the Early Iron Age graves of Daba (Dibbā, Sultanate of Oman) (poster) - Caputo, Francesco Paolo; Genchi, Francesco (Proceedings of the Seminar for Arabian Studies, 2016)
Discoveries of shell discs from Daba, Sultanate of Oman (c.1500–800 BC) will allow a detailed and comprehensive description of a group of poorly understood artefacts. All such discs were perforated on the back sides with a series of converging holes, while a few of them were decorated with a combination of incisions and carvings. Only rarely have similar objects been discovered in contemporaneous and later archaeological contexts in eastern Arabia. The research for this poster paper explored the meaning of both the function and origin of these seashell discs, combining morphological and stylistic descriptions with archaeo-metric analyses and experimental studies.